Allochthonous and vagrant ichthyofauna in Hellenic marine and estuarine waters - CORSINI-FOKA, M.; ECONOMIDIS, P.S. (Mediterranean Marine Science, 2007)
A review of the non-indigenous ichthyofauna occurring in the Hellenic marine and estuarine waters is presented, including Atlantic origin colonizers, aquaculture introduced and Lessepsian alien species. 34 non-native species have been registered. The majority of allochthonous fish are Lessepsian immigrants, which represent approximately 80% of the ascertained non-native ichthyofauna in Hellenic waters; their establishment, spread, habitat, abundance and interaction with indigenous fish are discussed.